Improving the Strength and Leaching Characteristics of Pb-Contaminated Silt through MICP - Fusheng Zha (MDPI AG, 2021)
Microbial-induced carbonate precipitation (MICP) is an effective technology for repairing sites contaminated by heavy metals. In this work, Sporosarcina pasteurii was cultured and mixed with a cementing fluid as a binder to remediate Pb-contaminated silt. The effects of varying experimental parameters, including Pb concentration and dry density, were also tested and analyzed. The leaching and strength characteristics and the MICP improvement mechanism of the Pb-contaminated silt were studied. Samples with dry densities of 1.50 g/cm3 and 1.55 g/cm3 exhibited the highest unconfined compression strengths (UCS). Scanning electron microscopy showed that not all CaCO3 crystals produced a cementation effect, with some filling pores in an invalid cementation form. The results showed that MICP remediation of low Pb2+ concentration-contaminated silt could meet the relevant Chinese environmental safety standards. Low Pb concentrations helped improve MICP-treated, Pb-contaminated silt strength, whereas high Pb concentrations significantly reduced this strength. Testing to determine the tolerance of an active microbe, Sporosarcina pasteurii, showed that trace amounts of Pb promoted its growth, thus improving the MICP effect, whereas excessive Pb had a toxic effect, which reduced MICP effectiveness. Mercury injection experiments showed that MICP produced CaCO3; this mainly filled soil mesopores and macropores and, thus, improved the soil UCS. Scanning electron microscopy showed that not all CaCO3 crystals produced a cementation effect, with some filling pores in an invalid cementation form. MICP was innovatively applied to silt sites with heavy metal pollutants while considering the soil compaction in actual construction, thus broadening the application scope of MICP, optimizing the construction process, and reducing the construction cost.